KARAKTERISASI SENSOR DARI KUBIS MERAH UNTUK MENDETEKSI KESEGARAN BUAH PEPAYA POTONG - Yunita Handoyo, Diana Lady (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
Cut papaya is an example of cut fruit sold in supermarkets. Cut papaya is easily degraded in quality, so an indicator is needed that can detect the freshness of cut papaya. Red cabbage as a plant source of natural pigments, namely anthocyanins, can be applied as a natural indicator because of its nature that can change color in response to changes in pH. The red cabbage sensor was characterized including response time, lifetime, and reproducibility. The red cabbage indicator was prepared by immobilizing Whatmann filter paper in red cabbage extract. The immobilized indicator was aired and then the average blue value was measured using ImageJ. The sensor response time was 4 minutes, the sensor lifetime was 12 days and the sensor showed good reproducibility because the RSD value of the mean blue was <10%.